ANALISA PERFORMA MESIN DIESEL DENGAN BAHAN BAKAR BIODIESEL DARI MINYAK JARAK PAGAR - Samsudin Raharjo (JURNAL LITBANG, 2007)
Plant oil is one of the potential plant resources as hidro carbon or energy source in Indonesia. Nevertheless, the oil can nol be used automatically because of having high viscosity, lower octan number, free fat, lower volatility, gum, and higher residue if it is used as ready to use fuel. There fore it has to be changed to another form, that is, to be alkil ester ( biodiesel ).Biodiesel usage still uses solar fuel as mixture. In this research, it is found that performance dffirence between solar and biodisel and biodiesel use usage.fully.Diesel machine performance which wants to be researched is machine torsion generated by diesel machine using solar fuel and resulted by diesel machine by using different fuel.As preliminary study, testing used in injection system diesel machine is when machine in stationer or netral condition, and diesel fuel used is biodisel made of jarak pagar oil.Ester oil usage as biodiesel fuel is based on temporary prediction that biodiesel with jarctk pagar oil fuel does not need solar fuel mixture and need diesel machine modification.Keywords : Biodisel, Diesel Machine, and Machine Torsion.